PERANGKAT AJAR PENGENALAN CHORD PADA ALAT MUSIK GITAR, KEYBOARD DAN RECORDER - Ivan Susanto (Universitas Catur Insan Cendekia (CIC) Cirebon, 2017)
Abstract Advances in information technology allows its utilization in various fields, one of which is the field of music. The high cost of studying music in music course institutions is an obstacle for those who want to learn musical instruments and Chords. Therefore, by utilizing technological progress here the author tries to collect material about music from various sources, especially in the field of Chord recognition on guitar instruments, Keyboards and Recorders. The goal itself is that this tool can help users understand Chords, how they sound, and how to play the Chords on guitar, Keyboard and Recorder instruments to make it easy to learn music. Keywords : Music, teaching device, guitar, Keyboard, Recorder